Is Laparoscopic Pyeloplasty for Ureteropelvic Junction Obstruction in Infants Under 1 Year of Age a Good Option? - Zamfir Snykers, Corina; De Plaen, Elea; Vermersch, Sophie; Lopez, Manuel; Khelif, Karim; Luyckx, Stephane; Philippe, Paul; Varlet, Francois; Steyaert, Henri (Frontiers in Pediatrics, 2019)
Purpose: Laparoscopic pyeloplasty in children younger than 1 year of age is still debatable due to its supposed technical difficulties and failure rate. We present our experience and outcome in infants. Material and Methods: A retrospective study was conducted in 3 Departments of Pediatric Surgery. We reviewed the records of the children under 1 year of age operated on for ureteropelvic junction obstruction (UPJO), between 2007 and 2017. Anderson-Hynes laparoscopic transabdominal dismembered pyeloplasty was performed. Patients demographics, results of preoperative and postoperative studies, perioperative details, complications, hospital stay and long-term follow-up results were analysed. Results: Sixty cases were operated on during this period (49 boys, 11 girls). Mean age at operation was 4.5 months (1-12 months). Mean operating time was 140 min (80-240min). There was no conversion in this group. There were 4 early complications: 1 ileus, 1 hypertension immediately post-operatively requiring medical treatment, 1 omental herniation through a drain orifice and 1 percutaneous transanastomotic stent migrated intra-abdominally. The 2 last children had to be reoperated. Mean hospital stay was of 2 days (1 to 10 days). Late complications: 2 patients (3.4%) presented a recurrence of UPJO, 1 had been re-operated 15 months later and for the patient with persistent hypertension, nephropexie was performed in malrotated kidney, 1 year after pyeloplasty. Long term follow-up with a mean of 2.8 years (1 to 10 years) showed that surgery improved mean pelvic dilatation from 31.8mm (13 to 63 mm) preoperatively to 15.3 mm (4 to 40 mm) postoperatively (P<0,0001). The renal function slightly improved, from a mean of 35,7% (5%-55%) it passed to 40,5% (0%-54%), p=0,137. In 3 cases the operated kidney became finally nonfunctional and atrophic. Conclusions: Laparoscopic transperitoneal pyeloplasty is feasible and safe in children younger than 1 year of age. Nevertheless, it requires experience and good intra-abdominal suturing skills. Laparoscopic pyeloplasty has a success rate comparable with open treatment but with less morbidity and better cosmetic results.